THE CONTRIBUTION OF THE PSYCHOLOGY OF RELIGION AND SPIRITUALITY TO THE DEVELOPMENT OF SUSTAINABILITY IN SMART CITIES: A CONTRIBUIÇÃO DA PSICOLOGIA DA RELIGIÃO E DA ESPIRITUALIDADE NO DESENVOLVIMENTO DA SUSTENTABILIDADE EM CIDADES INTELIGENTES - Bianchini Porfírio, Gustavo (2024)
Considering religion and spirituality as essential components of the human experience and also associated with better mental health, a discussion is carried out regarding their impact on the development of sustainability in Smart Cities. The aim of the study is to identify the application of the Psychology of Religion and Spirituality in aligning these areas with the proposal of the SDG-3 for Cities. An integrative review methodology was used in 23 relevant studies that promote discussion on the Psychology of Religion and Spirituality in the context of smart and sustainable cities. These studies were selected based on pre-defined inclusion and exclusion criteria, with data collection for subsequent analysis. It was observed that aspects such as interconnection, values and ethics, and health and well-being are facets of religion and spirituality that can be integrated into the construction of smart cities. Religion and spirituality can play a crucial role in shaping smart cities and offer pathways for sustainability to be achieved. Further studies on the topic and its application in smart city development projects can better explore this interaction.